Green marketing for eco-friendly vegetable products at Wanita Tani Karya Manunggal Group - Saptaningsih Sumarmi; Okti Purwaningsih; Meilany Nonsi Tentua; Aprilia Tita Wahyuningsih; Muhammad Adilah; Hani Andrasari; Kumala Dewi Retno Astuti; Nur Azizah Aprilia (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Green marketing is a marketing concept that carries the green concept, considering the environment in terms of green products, green prices, green places, and green promotional activities carried out. This service activity was carried out in Sawahan Hamlet, Pandowoharjo village, Sleman district, with the target participants being KWT Karya Manunggal members. This activity aims to increase participants' understanding and apply green marketing from environmentally friendly vegetables produced by KWT activities. Implementing FGD activities is face-to-face, accompanied by questions and answers, and assistance until the product is ready to be marketed. The participants enthusiastically followed the service activities, and KWT Karya Manunggal succeeded in having a logo used as a brand in marketing products. In addition, the team succeeded in obtaining the copyright for environmentally friendly vegetable packaging from DJKI under the Ministry of Law and Human Rights. To expand the market, social media is used to reach a broader range of consumers by presenting images of dancing products, thereby reducing physical contact with consumers.